2021
DOI: 10.1042/bsr20204247
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of An-Chuan Granule for the treatment of asthma based on a network pharmacology approach and experimental validation

Abstract: An-Chuan Granule (ACG), a traditional Chinese medicine (TCM) formula, is an effective treatment for asthma but its pharmacological mechanism remains poorly understood. In this study, network pharmacology was applied to explore the potential mechanism of ACG in the treatment of asthma. The tumor necrosis factor (TNF), toll-like receptor (TLR), and Th17 cell differentiation-related, nucleotide-binding oligomerization domain (NOD)-like receptor, and NF-kappaB pathways were identified as the most significant signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
(53 reference statements)
2
3
0
Order By: Relevance
“…is is consistent with the results of Chen et al's study that the mRNA and protein levels of caspase 1 were upregulated in the lungs of asthmatic mice induced by OVA, leading to an inflammatory response [37].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…is is consistent with the results of Chen et al's study that the mRNA and protein levels of caspase 1 were upregulated in the lungs of asthmatic mice induced by OVA, leading to an inflammatory response [37].…”
Section: Discussionsupporting
confidence: 93%
“…These results suggested that MDSCs exacerbated pneumonitis, mutagenesis, pulmonary fibrosis, and cell apoptosis in OVA-induced asthmatic mice. This is consistent with the results of Chen et al's study that the mRNA and protein levels of caspase 1 were upregulated in the lungs of asthmatic mice induced by OVA, leading to an inflammatory response [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…A network pharmacology strategy has been adopted for investigating the mechanism of action underlying the effectiveness of Chinese drugs 68 and TCM formulas. 69 , 70 To some extent, the application of network pharmacology will accelerate the research process of TCM in asthma. In addition, essential oils contained in medicinal plants with proven antiasthmatic properties have the possibility of being used as bronchodilators, mast cell stabilizers, expectorants, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Through the TCM database (http://www.organchem.csdb.cn/scdb/default.htm) and disease database (https://phgkb.cdc.gov/; Chen et al, 2021; Zuo et al., 2018), we compared the target genes of TCDCA and disease genes of gastric cancer and found 90 TCDCA target genes, 928 disease genes of gastric cancer and 28 overlapping genes. This finding suggests that TCDCA may affect the carcinogenesis of gastric cancer by regulating the function of some genes.…”
Section: What Is Known and Objectivementioning
confidence: 99%